Philadelphia Freedoms : Black American Trauma, Memory, and Culture after King. - Awkward, Michael (Philadelphia : Temple University Press, 2013)
Michael Awkward's Philadelphia Freedoms captures the energetic contestations over the meanings of racial politics and black identity during the post-King era in the City of Brotherly Love. Looking closely at four cultural moments, he shows how racial trauma and his native city's history have been entwined. He introduces each of these moments with poignant personal memories of the decade in focus and explores representation of African American freedom and oppression from the 1960s to the 1990s. Philadelphia Freedoms explores NBA players' psychic pain dur.
Conclusion: No Longer at Home?Notes; References; Index.
Print version record.
JSTOR
Keywords: American fiction -- African American authors -- History and criticism; African Americans -- Intellectual life; Collective memory in literature; Psychic trauma in literature; Roman américain -- Auteurs noirs américains -- Histoire et critique; Noirs américains -- Vie intellectuelle; Mémoire collective dans la littérature.; Traumatisme psychique dans la littérature.; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM -- General; African Americans -- Intellectual life; American fiction -- African American authors; Collective memory in literature; Psychic trauma in literature; Schwarze; Kultur; Literatur; Rassenpolitik; Kollektives Gedächtnis; Psychisches Trauma; USA; Philadelphia, Pa; Criticism, interpretation, etc